2013
DOI: 10.1063/1.4798657
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-assisted high reflectivity and strong magneto-optical Kerr effect in permalloy gratings

Abstract: We demonstrate experimentally a strong plasmon-assisted enhancement of the transverse magneto-optical Kerr effect in permalloy gratings. The enhanced transverse magneto-optical Kerr effect is accompanied by an increased grating reflectivity with the maximum of enhancement being correlated with plasmonic Fano resonances. This correlation was confirmed by an intuitive Fano model and also through full-vectorial optical simulations. Simultaneously high reflectivity and transverse magneto-optical Kerr effect as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…In magneto-plasmonic nanostructures the enhanced TMOKE response is compromised by a relatively low reflectivity of ∼ 20 − 25% (see, e.g., [8,11]). Furthermore, in our work [9] we have shown that the maximum of the TMOKE response occurs at the frequency of the Fano resonance. Due to the asymmetry of the line shape of Fano resonances the maximum of the TMOKE response is often shifted from the maximum of the reflectivity towards its minimum.In this paper, we demonstrate theoretically a large TMOKE response in subwavelength gratings consisting of alternating magneto-insulating and nonmagnetic dielectric nanostripes.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…In magneto-plasmonic nanostructures the enhanced TMOKE response is compromised by a relatively low reflectivity of ∼ 20 − 25% (see, e.g., [8,11]). Furthermore, in our work [9] we have shown that the maximum of the TMOKE response occurs at the frequency of the Fano resonance. Due to the asymmetry of the line shape of Fano resonances the maximum of the TMOKE response is often shifted from the maximum of the reflectivity towards its minimum.In this paper, we demonstrate theoretically a large TMOKE response in subwavelength gratings consisting of alternating magneto-insulating and nonmagnetic dielectric nanostripes.…”
supporting
confidence: 52%
“…Finally, we refer to Fig. 3(a) in our work [9] where we investigate a Py grating of the same period as the subwavelength dielectric grating. However, instead of Si the Py grating has air grooves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much smaller values of a control magnetic field are feasible if the plasmonic crystal includes magnetic materials, which is referred to as magneto-plasmonic crystal (MPC). Such an MPC provides outstanding magneto-optical properties as evidenced by significant enhancements of the Faraday and transverse Kerr effects192021222324252627282930. The mostly pronounced enhancement of the magneto-optical effects was found for MPCs containing a perforated noble metal stacked on a magnetic dielectric film27282930.…”
mentioning
confidence: 98%
“…Note that only the structures in Panels (a) and (b) were designed to operate as optical devices. Although the structures in the remaining Panels were not designed as such, their metallic nanostructures allow employing them as optical devices, which opens up opportunities for the integration of nanophotonics and nano-magnetism [26,60].…”
Section: Figmentioning
confidence: 99%